INFLUÊNCIA DO USO E OCUPAÇÃO DA TERRA SOBRE OS MACROINVERTEBRADOS AQUÁTICOS E A QUALIDADE DA ÁGUA NA BACIA HIDROGRÁFICA DO RIO DAS ANTAS, IRATI-PR - DARIVA, CARLA MALAVAZI (2021)
Aquatic macroinvertebrates are the most studied assemblages in stream communities to understand the effects of different types of land use and occupation and water quality. The objective was to evaluate the dynamics of the water quality of the Rio das Antas, based on physical-chemical, microbiological and macroinvertebrate parameters, considering the use and occupation of land along the entire hydrographic basin, including the influence of the urban portion of the municipality of Irati, from the receipt of effluent from the sewage treatment plant (ETE) and from the Irati National Forest. To determine the existence of these differences, water quality parameters, geographic information system techniques and aquatic fauna diversity indices were used, using macroinvertebrates, which are bioindicators. Macroinvertebrates and water were collected at 19 points, including 8 in Rio das Antas and 11 in tributaries, seeking to cover the different levels of land use and occupation. The classification of land use, division, delimitation of basin areas, calculation of land use and occupation rates was carried out. In addition, the level of preservation of the ecological conditions of the collection points was evaluated using the Rapid Assessment Protocol. To assess water quality, physicochemical and microbiological analyzes of the water were performed using the IQA. The results were also compared with CONAMA Resolution No. 357/05, for a Class 2 river. To characterize the macroinvertebrates, Shannon-Wiener (H'), Pielou's Equitability (J), Margalef's Wealth indices were used, BMWP', % EPT and %Chironomidae. Canonical Correspondence Analysis (CCA) was used to assess the relationships between macroinvertebrate communities and the environmental variables of water quality and rates of land use and occupation. CCA revealed a quality division on the first axis. All diversity and water quality indices were, in general, higher for the basins in protected forests, with a higher rate of occupation by areas of native forest and reforestation, being intermediate in rural basins, with areas of agricultural use and occupation with less fragmented riparian vegetation, and the worst rates were in urban basins, with areas with greater urban influences and within the urban perimeter. Results that reinforce the influences caused on water bodies by land use and occupation, directly affecting the aquatic macroinvertebrate community and water quality, especially in urban areas. These results are confirmed by the relationships of the environmental variables with the macroinvertebrate community obtained in the CCA. It was concluded that the conservation unit effectively contributes to the conservation of the diversity of aquatic macroinvertebrate fauna, but the conservation unit was not sufficient to recover the water quality in the Rio das Antas hydrographic basin, to meet the limits imposed by legislation.